Korelasi Disparitas Tenaga Kesehatan Puskesmas Terhadap Pelayanan Kesehatan Primer Peserta Jaminan Kesehatan Nasional Kabupaten Poso - Ryandti Ruslang Ruslang; Diah Ayu Puspandari (Jurnal Jaminan Kesehatan Nasional, 2023)
Poso Regency is one of the regions that has achieved universal health coverage. However, based on the data from BPJS Kesehatan in 2022, the percentage of participants referred with non-specialistic diagnoses from Primary Health Care Facilities (FKTP) is still significant. This is related to the role of FKTP as a gatekeeper in primary care services. This research aims to describe the performance of Puskesmas as gatekeepers in controlling referrals by linking the availability of healthcare personnel to referral rates. This research is a quantitative approach with secondary data sourced from BPJS Kesehatan. It was found that the p-value for the ratio of doctor is very borderline (0.05) concerning the number of referrals. Additionally, there were 586 referrals with specialized diagnoses that were eventually coded as non-specialistic diagnoses in hospitals, with 210 of them coded as H.521, which should have been managed at the Puskesmas. It is recommended that the central government consider the distribution of healthcare personnel from outside the region through temporary work agreements. Furthermore, based on the significant number of non-specialistic referrals, particular attention should be given to referrals to the eye clinic (Poli mata), which may be indicative of eyeglass services. Therefore, it is advisable to consider policy changes so that participants seeking eyeglasses can undergo examinations at the community health centers according to the standard competency of doctors, supplemented by supporting training to ensure certified practitioners conduct the examinations.